Distributions of particulate and dissolved phosphorus in aquatic habitats of Peninsular Malaysia - Lim, Joon Hai; Lee, Choon Weng; Bong, Chui Wei; Affendi, Yang Amri; Hii, Yii Siang; Kudo, Isao (Elsevier, 2018)
Particulate phosphorus was the dominant phosphorus species and accounted for 72 ± 5% of total phosphorus in coastal habitats, 63 ± 4% in estuaries, 58 ± 6% in lakes and 80 ± 7% in aquaculture farms whereas dissolved inorganic phosphorus (DIP) and dissolved organic phosphorus (DOP) were minor components. Correlation analyses (DIP vs Chl a; R2 = 0.407, df = 31, p < 0.001) suggested phosphorus limiting conditions in lakes, which was corroborated with the highest alkaline phosphatase activity (APA) that fluctuated from 0.38 to 41.14 nmol L−1 min−1. In contrast, APA was elevated in coastal habitats and estuaries only when DIP concentration decreased below 0.9 μM. Moreover size-fractionation experiment showed that the highest APA was detected in the 0.2–2 μm pico-size fraction. Our results suggested that the main APA in coastal habitats and estuaries was from phototrophic pico-eukaryotes and heterotrophic bacteria, and regulated largely by DIP availability.